Giardia lamblia infection induces changes in the biochemical profile of gerbils (Meriones unguiculatus) - Gil, Frederico F; Mendes, Gabriel Moreira de M; Teixeira, Marcia C Aquino; Oliveira, Dirce R; Cruz, Ruth E; Santos, Joseph F G; Gomes, Maria Aparecida (The Journal of Infection in Developing Countries, 2025)
Introduction: Giardia lamblia is a global parasite that infects both humans and animals. However, its pathogenic mechanisms remain poorly understood. Infected children, in particular, may exhibit deficits in physical and cognitive development. To better comprehend the metabolic changes associated with the disease, this study investigated the biochemical profile of gerbils experimentally infected with the Portland strain of G. lamblia Methodology: Sixteen gerbils, equally divided by sex, were included in the experiment for 35 days, with blood samples collected every 7 days. Results: blood glucose and insulin levels increased on the 21st day post-infection (DPI), suggesting persistent inflammation and increased insulin resistance. Additionally, there was a progressive decrease in total protein with a paradoxical increase in albumin, indicating a state of anabolism in response to infection. Alkaline phosphatase, AST, and ALT levels remained unchanged, suggesting that liver function was not affected by the infection. Cortisol levels increased from the 7th DPI onwards, while calcium, cholesterol, and triglyceride levels began to increase from the 21st DPI onwards. Conclusions: These findings confirm the systemic inflammatory state induced by giardiasis and highlight significant metabolic alterations in experimentally infected animals. Further research is warranted to elucidate the pathophysiological mechanisms underlying these metabolic disturbances.